Flaviviruses—Induced Neurological Sequelae - Samantha Gabrielle Cody; Awadalkareem Adam; Andrei Siniavin; Sam S. Kang; Tian Wang (Pathogens)
Flaviviruses, a group of single-stranded RNA viruses spread by mosquitoes or ticks, include several significant neurotropic viruses, such as West Nile virus (WNV), Japanese encephalitis virus (JEV), tick-borne encephalitis virus (TBEV), and Zika virus (ZIKV). These viruses can cause a range of neurological diseases during acute infection, from mild, flu-like symptoms to severe and fatal encephalitis. A total of 20–50% of patients who recovered from acute flavivirus infections experienced long-term cognitive issues. Here, we discuss these major neurotropic flaviviruses-induced clinical diseases in humans and the recent findings in animal models and provide insights into the underlying disease mechanisms.